Understanding the Politics of Climate Security Policy Discourse: The Case of the Lake Chad Basin. Issue 3 (27th May 2023) - Daoust, Gabrielle; Selby, Jan
ABSTRACT: Policy discourse on the conflict and security implications of climate change has repeatedly found it to be overstated, misleading, and out of line with the balance of scientific evidence. However, the reasons for this recurring science-policy divide have not yet been systematically investigated. To explore this issue, we examine the case of Lake Chad, which over the last decade has become a poster child for climate conflict. We seek to understand and explain how this climate security narrative has gained such traction. Drawing on interviews and documentary analysis we examine the key practices, interests and hierarchies underpinning the narrative's rise and reproduction, and show that it is essentially a political construct, reflecting a combination of questionable epistemic manoeuvres and geopolitical, economic and climate mitigation agendas. Our findings suggest the need for change, and increased caution, in how the climate security community engages with scientific evidence.